CHARACTERIZATION AND IDENTIFICATION OF SM4 BACTERIAL ISOLATE FROM Stylissa massa SPONSE AS PRODUCING ANTIMICROBIAL COMPOUNDS AGAINST PATHOGENIC BACTERIA - Lukas Pardosi (BERITA BIOLOGI, 2022)
East Nusa Tenggara (NTT) is one of the archipelagic provinces in Indonesia with a sea area of 200,000 km² and contains potential marine resources including the Stylissa massa sponge. Bacteria have been known to associate with sponges and have the ability to produce antimicrobial compounds. This study aims to characterize, identify the 16S rRNA gene, and test the bioactive compounds of SM4 bacterial isolates from the Stylissa massa sponge. The bacterial isolates of SM4 were previously rejuvenated on NA medium, then characterized by macroscopic morphology, and biochemistry by citrate test and TSIA test. The culture was extracted using petroleum ether solvent and the antibacterial activity was tested against E. coli and S. aureus by the well method. The isolates were then identified based on the 16S rRNA gene by PCR method. The results showed that, SM4 isolates had small colony size, yellow color, round colony shape, flat elevation, flat margins, while biochemically they had positive results with Citrate and TSIA tests. The antagonist test of the SM4 bacterial isolate was found to have the ability to inhibit the growth of S. aureus and  E. coli, while the antibacterial activity test of the bioactive compound bacterial isolate SM4 was known to have the ability to inhibit the growth of S .aureus with an inhibition zone of 1.99 mm and E. colli 1.56 mm. The results of the molecular identification of the bacterial isolate SM4 had 99% similarity with the Bacillus cereus strain Nr_074540.1